PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Kasus Bagian Operasional PT. Indah Logistik Cargo Cabang Pekanbaru) - Prastika Meilany; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Discipline is the function of human resource management is paramount and the realization of the key goals for without discipline both difficult to achieve maximum goals. Sources success of a company in producing high performance workforce is qualified and have adequate working effectiveness. As for which is included into the discipline of work in this research is punctuality, obedience to the rules, and the ability to maintain office equipment.Performance is the result of the work accomplished by someone the job requirements. The results of the quality and quantity of performance achieved by employees in carrying out their duties in accordance with the responsibilities assigned to him. The factors that affect the performance is the ability and motivation.PT. Indah Logistik Cargo Pekanbaru branch is one of the services company engaged in shipping services. The operational part is the most important part of the company, in which the operational part directly interact with consumers in serving service delivery, and in the operational part is required of employees who have the ability and high motivation for the sake of undergo work and meet its targets.Based on the analysis of this study showed that there is a strong influence between disciplines working with employee performance of the operations of PT. Indah Logistik Cargo Pekanbaru branch. It can be seen from the analysis of known data from the t (13.637)> t table (1.997) and Sig (0,000) <0.05. Then the hypothesis is no influence on the performance of the employees work discipline is acceptable.Keyword: Discipline Work, Employee Performance